Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus, Dan Dana Bagi Hasil Terhadap Pertumbuhan Ekonomi Serta Indeks Pembangunan Manusia Di Maluku Utara - Rubiyanto Rubiyanto; Prince Charles Heston Runtunuwu*; Amran Husen (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Economic growth shows the extent to which economic activity will generate additional public income in a certain period, that is, an economy is said to experience growth if the real income of the community in a certain year is greater than the real income of the community in the previous year. Economic growth is the most important factor in development that determines the success of the development of a region/region which is measured based on the high or low levels of economic growth achieved. This study aims to analyze the effect of General Allocation Funds (DAU), Special Allocation Funds (DAK) and Revenue Sharing Funds (DBH) on Economic Growth and Human Development Index (IPM). The object of research was carried out in South Halmahera Regency in 2012-2021 using the multiple linear regression analysis testing method. The results show that the influence of the General Allocation Fund, the Special Allocation Fund and the Profit Sharing Fund simultaneously influence Economic Growth with the Human Development Index in South Halmahera Regency. While the results of partial testing, the influence of General Allocation Funds, Special Allocation Funds and Profit Sharing Funds also affect Economic Growth with the Human Development Index in South Halmahera Regency. This indicates that the greater the regional potential revenue, it will be able to increase the achievement of Economic Growth and the Human Development Index.